Sociodemographic and psychological factors as predictors of body mass index-for-age (BAZ) among adolescents in Sibu, Malaysia - Law, Leh Shii; Gan, Wan Ying; Mohd Taib, Mohd Nasir (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Understanding childhood obesity becomes vital as a tremendous increase in the prevalence of overweight/obesity among children and adolescents was observed. This cross-sectional study aimed to investigate the associations between sociodemographic and psychological characteristics with body-mass-index-for-age (BAZ) among adolescents in Sibu, Sarawak. Methods: A total of 375 students (32.0% males and 68.0% females; 15-17 years old) at four randomly selected public secondary schools were recruited. A questionnaire on sociodemographic and psychological characteristics (self-efficacy for physical activity, weight management, and nutrition, body discrepancy score, and sociocultural pressure to be thin) were used to gather information. Body weight and height were also assessed. Results: Around 18.6% respondents were found to be overweight/obese while nearly 5.0% were categorized as thin. In multiple linear regression, three significant predictors, namely body discrepancy score, being Iban (Reference: Chinese) and sociocultural pressure to be thin explained 45.1% of the variance in BMI-for-age z-score. Conclusion: Future interventions on adolescent body weight management should consider incorporating sociodemographic and psychological factors such as the development of positive body image, uniqueness in cultural value, and management of perceived sociocultural pressures to increase their effectiveness.